2013
DOI: 10.1155/2013/870814
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Considerations in Conducting an Olfactory fMRI Study

Abstract: The sense of smell is a complex chemosensory processing in human and animals that allows them to connect with the environment as one of their chief sensory systems. In the field of functional brain imaging, many studies have focused on locating brain regions that are involved during olfactory processing. Despite wealth of literature about brain network in different olfactory tasks, there is a paucity of data regarding task design. Moreover, considering importance of olfactory tasks for patients with variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…26 Our finding of decreased brain activation in the bilateral temporal cortex and left superior parietal lobule of patients with traumatic anosmia in response to an unpleasant odor is consistent with previous observations. [27][28][29] Although olfaction primarily functions as a means for odor perception and identification, it also serves an additional function in understanding and integrating multimodal actions. 27 A previous fMRI study that used visual and olfactory stimuli reported increased activation in the middle temporal gyrus and parietal cortex (areas of multisensory integration) during stimulation, supporting the idea that olfaction serves multiple functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Our finding of decreased brain activation in the bilateral temporal cortex and left superior parietal lobule of patients with traumatic anosmia in response to an unpleasant odor is consistent with previous observations. [27][28][29] Although olfaction primarily functions as a means for odor perception and identification, it also serves an additional function in understanding and integrating multimodal actions. 27 A previous fMRI study that used visual and olfactory stimuli reported increased activation in the middle temporal gyrus and parietal cortex (areas of multisensory integration) during stimulation, supporting the idea that olfaction serves multiple functions.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Although olfaction primarily functions as a means for odor perception and identification, it also serves an additional function in understanding and integrating multimodal actions. 27 A previous fMRI study that used visual and olfactory stimuli reported increased activation in the middle temporal gyrus and parietal cortex (areas of multisensory integration) during stimulation, supporting the idea that olfaction serves multiple functions. 28 Furthermore, activation in the temporoparietal cortex has also been associated with odor-recognition memory, a task with a high cognitive demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that investigate the effects of olfactory disorders on functional activity in the olfactory system during the administration of odors in general show decreased activation in olfactory areas of the brain (Vedaei et al, ). Changes in brain activity after smell loss have been investigated extensively in patients suffering from neurodegenerative disorders, like Alzheimer's disease (Cerf‐Ducastel & Murphy, ; Wang et al, ) and Parkinson's disease (Welge‐Lüssen et al, ), and in aging patients (Welge‐Lüssen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another innovative approach employs pinch valves and miniature valve terminal assemblies located close to the participant, both reducing transition times and device footprint (Bestgen et al, 2016). Finally, Vedaei et al (2013) present a review of issues involved in conducting fMRI studies of olfaction. These authors address expected response times and brain locations; issues of habituation, adaptation, concentration, and number of odor presentations; and applications to diseases such as Alzheimer’s disease, Parkinson’s disease, schizophrenia, and clinical depression.…”
Section: Introductionmentioning
confidence: 99%